Waste plastic derived reduced graphene oxide as a potential additive for the surfactant polymer flooding: A sustainable solution - Pandey, Anurag; Kesarwani, Himanshu; Tewari, Chetna; Saxena, Amit; Sharma, Shivanjali; Sahoo, Nanda Gopal (Elsevier BV, 2023)
The twenty-first century's major problems are the demand for sustainable green energy and the eco-friendly upcycling of plastic waste. The solutions to these problems should have an alluring cost-effective industrial synergy. Tackling these issues address the clean energy generation concerns and the long-term preservation of the economy and environment from plastic waste. This study focuses on upcycling waste plastics into reduced graphene oxide (RGO) and their application in enhanced oil recovery. Raman and TEM analysis confirmed the successful synthesis of RGOs. In addition, FTIR helps study the presence of functional groups and TGA for thermal stability analysis. The RGO improves the oil recovery by altering wettability, reducing surface tension / interfacial tension, and minimizing surfactant loss. The surface / interfacial property and wetting attributes of the RGO-based prepared solution were examined by surface tension and contact angle measurement. The surface tension and contact angle reduction using RGO were-25% and-20% without surfactant. Whereas with sur-factant (anionic, cationic, and nonionic) and RGO, the reduction in surface tension was-55%,-57%, and-57%, respectively. Also, the reduction in contact angle with surfactant was-83%,-46%, and-80% for anionic, cationic, and nonionic surfactant with RGO particles. The chemical slug's viscosity was then examined at elevated temperatures. The viscosity results follow the power law model to comprehend fluid flow behavior. Finally, the chemical slug consisting of a surfactant mixture, RGO particles, and an industrial-grade polymer was used in the sand pack flooding studies recovering-71% of the original oil in place.